Pembuatan Database Desa Berbasis Masyarakat Bagi Masyarakat Desa Jetislor Pacitan - Mustangin, Mustangin; Sari, Andareka Murih Aditya; Islami, Nufa Pramina; Kusniawati, Desy; Setyoningrum, Baruna; Istirochmana, Lina; Kurniawan, Danang; Saputri, Era Dewanti; Meilianawati, Hesty; Prasetyawati, Eni (Universitas Muhammadiyah Surabaya, 2019)
Database Development Program is one of the activities of Practice Experience (PPL) which is implemented as one of practice to provide experience for students. The program is structured to help the village Jetislor that do not have a database. Programs are implemented directly with the community through a learning approach. Implementation of the program begins with the establishment of database cadres and further training of cadres to provide knowledge and skills. The creation of a community-based database has contributed to the village government with its database containing information about the jetis lor village community. The characteristics of data used as content in this database are General Data, Family Data, Family Expenditure Data, Agricultural and Livestock Data, Social Information Data as additional data.